2004
DOI: 10.1002/cncr.20513
|View full text |Cite
|
Sign up to set email alerts
|

Some methodologic lessons learned from cancer screening research

Abstract: Credible and useful methodologic evaluations are essential for increasing the uptake of effective cancer screening tests. In the current article, the authors discuss selected issues that are related to conducting behavior change interventions in cancer screening research and that may assist researchers in better designing future evaluations to increase the credibility and usefulness of such interventions.Selection and measurement of the primary outcome variable (i.e., cancer screening behavior) are discussed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
1
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(101 citation statements)
references
References 101 publications
(197 reference statements)
6
92
1
2
Order By: Relevance
“…Other treatments of multilevel intervention research address measurement issues (28,60), but when assessing predictors or changes at different levels, measurement becomes much more complex than if there is only a single intervention at one level, no assessment of intervening variables, and only patient-level outcomes (61). In our example, if one is interested in the impact of a clinic-level intervention on provider knowledge, and whether clinic changes and provider knowledge are related to screening use, then multiple levels of measurement are necessary.…”
Section: Measurement Considerationsmentioning
confidence: 99%
“…Other treatments of multilevel intervention research address measurement issues (28,60), but when assessing predictors or changes at different levels, measurement becomes much more complex than if there is only a single intervention at one level, no assessment of intervening variables, and only patient-level outcomes (61). In our example, if one is interested in the impact of a clinic-level intervention on provider knowledge, and whether clinic changes and provider knowledge are related to screening use, then multiple levels of measurement are necessary.…”
Section: Measurement Considerationsmentioning
confidence: 99%
“…These include ever, recency of use (eg, within the past 3 years), and compliance with guidelines (eg, repeat or regular). 62 The range of outcomes measured makes comparisons among studies challenging. Two studies comparing different operational definitions for mammography found that although prevalence estimates varied greatly, the different definitions had little effect on the patterns of association with correlates.…”
Section: Cervical Cancer Screeningmentioning
confidence: 99%
“…At a minimum, questionnaires need to provide clear definitions and measures to facilitate interpretation and enable comparisons with other studies. 62 To our knowledge only 2 studies to date have examined the test-retest reliability of self-reported Pap tests. 65,66 Massachusetts BRFSS data showed that nonwhite women reported Pap testing less consistently over time than white women.…”
Section: Cervical Cancer Screeningmentioning
confidence: 99%
“…The study was conducted in a closed healthcare setting where the outcome could be ascertained through administrative files, eliminating recall bias and overestimation of the outcome commonly found when using self-reported data. 26 …”
Section: Discussionmentioning
confidence: 99%